Factors related to choking under pressure in sports and the relationships among them - Murayama, T.; Sekiya, H. (International Journal of Sport & Health Science, 2015)
Factors related to choking under pressure during sports were investigated through a questionnaire survey and the relationship among the factors was examined. A questionnaire survey of choking was conducted among university students in sports-oriented school clubs (n=535). Exploratory factor analysis extracted 11 factors: changes in motor control and vicious circles, abnormal physical sensations, perceptual and cognitive confusion, introversion, self-consciousness, feelings of physical heaviness and weakness, conscious processing (attention to movements), passivity, feelings of physical fatigue, safety-oriented strategies, and heat sensations. An analytical model with nine factors, (excluding feelings of physical fatigue and heat sensations) as latent variables was constructed, and covariance structure analysis was performed. The results indicated the validity of the mechanistic model of choking, consisting of nine latent variables. According to the model, when self-consciousness, or abnormal physical sensations, had a high profile, conscious processing increased. Furthermore, it was confirmed that conscious processing affected changes in motor control and vicious circles, which led directly to a decline in motor performance. It was also indicated that abnormal physical sensations determined perceptual and cognitive confusion, or feelings of physical heaviness and weakness. On the other hand, when perceptual and cognitive confusion and feelings of physical heaviness and weakness had a high profile, passivity increased. High passivity caused changes in motor control and vicious circles. Moreover, increased passivity led to the adoption of a safety-oriented strategy that often caused changes in motor control and vicious circles. While previous studies have tried to explain choking only from the perspective of changes in attention, the above results suggest the following mechanistic model of choking, indicative of another perspective: Changes in psychological, physiological, and behavioral variables cause a decline in performance. Especially interactions between emotions and cognitions and the adoption of a strategy with a low risk of failure determine changes in motor control.